Is a road to sustainable use of non-renewable mineral raw materials possible? - V. Steinbach (Society for Mining, Metallurgy & Exploration, 2011)
Non-renewable mineral raw materials are grouped into three categories to investigate ways leading to sustainable use of natural resources: 1.) metallic resources, 2.) non-metallic resources with the exception of the fertilizer minerals, and 3) the fertilizer minerals for the nutrients nitrogen (N), potassium (K), and phosphorous (P). With the exception of minerals in Group 3 which are essential for plant growth, mankind does not need raw materials as such, only the intrinsic property of a material that fulfils a useful function. This is especially true for non-metallic materials. Metallic resources have the best chance to become renewable if one makes optimal use of the resources of the man-made technosphere. For the fertilizer elements K and N there does not exist a problem, because sea water or air respectively provide an inexhaustible source for them. This does not apply to P however. So P is serving as one of our apposite case studies for solving sustainability challenges. For all the challenges along the road from a non-sustainable to a sustainable resource economy technology can be envisioned to come to the rescue provided conditions that are considered to be essential for sustainable use for all natural resources-- affordable renewable energy and human ingenuity to find new solutions for functions, to optimize processes and to minimize losses-- are satisfied.